The environmental friendliness level of the trammel net in Kuala Langsa, Langsa City, Aceh Province. (December 2018) - Rahmah, A; Miswar, E; Ramadhan, A; Aprilla, R M
Abstract: The development of fishing activities in Kuala Langsa water can continually increase the number of trammel net. Statistical data showed that the number of trammel net in Langsa in 2013 was 84 units and the number increased to 152 units in 2016. The main target of trammel net is shrimp. Whereas in reality the most catches are fish, with different species, small sizes of fish and not sellable. The objective of the present study was to assess the enviromental friendliness level of trammel net to the environment. Data collection was carried out by experimental fishing, with 3 samples of purse seine ships and 3 catching trips each. The data collected were number of fishes, species and size of the length and weight of the fishes. Data were analyzed using Shannon diversity index, Simpson dominance index, and scoring analysis (based on the 9 criteria of CCRF (Code of Conduct for Responsible Fisheries) about the environmental friendliness level of fishing gear). The results showed that the catch species diversity index was average 0.80 (high diversity index; low fishing gear selectivity) and average of dominance index was 0.27 categorized as low dominance (no dominance of certain species). The total score of the enviromental friendliness level was 27 which means trammel net categorized as less friendly to the environment.